Geopolymer and method for solidifying radioactive waste liquid

CN119638301APending Publication Date: 2025-03-18BEIJING RES INST OF URANIUM GEOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964283.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The cured polymer has shortcomings in nuclide adsorption, body strength and long-term stability, making it difficult to effectively cure and stabilize the radioactive waste liquid.

Method used

The geopolymer formulations including metakaolin, slag, bentonite, glass fiber, nanosilica and composite alkali activators are used, and the nuclide adsorption properties and compressive strength and long-term stability of the cured body are improved by thermal activation.

Benefits of technology

The nuclide adsorption properties of the ground polymer, the compressive strength and long-term stability of the cured body are significantly improved, ensuring effective curing of a variety of radionuclides, and reducing the risk of nuclide leakage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of nuclear environmental protection, in particular to a geopolymer and a method for solidifying radioactive waste liquid. The geopolymer is prepared from the following raw materials: a main material, glass fibers, nano silicon dioxide and a composite alkali activator, the main materials are metakaolin, slag and bentonite. The bentonite has good adsorbability, expansibility and plasticity, and the adsorbability and stability of the geopolymer are enhanced by using the bentonite; the toughness and crack resistance of the geopolymer are improved by using the glass fiber; the nano silicon dioxide provides active adsorption sites and improves the adsorption selectivity. All the components cooperate with one another, so that the geopolymer is endowed with good nuclide adsorbability, and the compressive strength and long-term stability of a geopolymer solidified body are improved. The method has a good curing effect on various radionuclides (such as uranium, strontium, cesium and the like), and can effectively prevent the radionuclides from being leached.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nuclear environmental protection, in particular to a geopolymer and a method for solidifying radioactive waste liquid. Background Art

[0002] Geopolymer is a new type of inorganic polymer material. It is a material with a three-dimensional network structure formed by polycondensation of raw materials such as aluminosilicate under alkaline conditions. Its chemical structure is similar to that of zeolite, which is composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons connected by shared oxygen atoms to form a disordered, amorphous network structure. Geopolymers are gradually being used in many industrial fields because their main raw materials, such as kaolin, fly ash, slag, and activators such as water glass, are widely available and inexpensive. For example, they can be used as a substitute for cement in the construction industry, as a catalyst carrier in the chemical industry, and as a refractory, curing, and adsorption material.

[0003] Geopolymers also play an important role in the field of nuclear environmental protection. Their main application principle is to stably fix or adsorb radioactive nuclides in radioactive waste liquid into a solid matrix through a series of physical and chemical processes. In the actual application of solidified geopolymers, geopolymers are fully mixed with radioactive waste liquid, and the aluminosilicate network structure inside them will interact with radioactive nuclides in various ways. On the one hand, through physical adsorption, radioactive nuclides are adsorbed on the surface by utilizing their own rich pore structure; on the other hand, chemical precipitation and ion exchange processes are also carried out simultaneously, and radioactive nuclides are exchanged with metal cations in geopolymers, or react with other components to form insoluble precipitates, which are finally firmly wrapped in the three-dimensional network structure, thereby greatly reducing the mobility and leaching of radioactive nuclides, effectively preventing pollution to the environment, and achieving harmless treatment of radioactive waste liquid.

[0004] However, solidified geopolymers still have some disadvantages, such as the adsorption of radionuclides needs to be improved, the strength of the solidified body is not high, and the long-term stability is poor. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a geopolymer and a method for solidifying radioactive waste liquid. The geopolymer has good nuclide adsorption, high compressive strength of the solidified body and good long-term stability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a geopolymer, comprising the following preparation raw materials: a main material, glass fiber, nano silicon dioxide and a composite alkali activator;

[0008] The main ingredients are metakaolin, slag and bentonite; the mass ratio of the metakaolin, slag and bentonite is 1:1:0.375;

[0009] The mass of the glass fiber is 2% of the total mass of the main material;

[0010] The mass of the nano silicon dioxide is 3% of the total mass of the main material;

[0011] The mass of the composite alkali activator is 15% of the total mass of the main material.

[0012] Preferably, the composite alkali activator comprises solid water glass and alkali metal hydroxide;

[0013] The modulus of the solid water glass is 1.5 to 2.0;

[0014] The mass ratio of the solid water glass to the alkali metal hydroxide is 5:1.

[0015] Preferably, the mass content of montmorillonite in the bentonite is above 70%.

[0016] Preferably, the metakaolin is obtained by dehydrating kaolin and then subjecting it to secondary calcination; the temperature of the secondary calcination is 800-900° C., and the time is 2-4 hours.

[0017] The present invention provides a method for solidifying radioactive waste liquid by using a geopolymer as described in the above scheme, comprising the following steps:

[0018] The main material, glass fiber, nano silicon dioxide and composite alkali activator are mixed to obtain a mixture;

[0019] mixing the mixed material with radioactive waste liquid to obtain a geopolymer slurry;

[0020] Curing the geopolymer slurry into a shape to obtain a first cured body;

[0021] The first solidified body is subjected to a heat activation treatment.

[0022] Preferably, the mass of the radioactive waste liquid is 30-50% of the total mass of the main material.

[0023] Preferably, the temperature of the thermal activation treatment is 200-600° C. and the time is 2-12 hours.

[0024] Preferably, the rate of heating to the temperature of the thermal activation treatment is below 5°C.

[0025] Preferably, after completing the heat activation treatment, the method further includes coating a coating material on the surface of the obtained second solidified body; if there are holes and / or cracks on the surface of the obtained second solidified body, the second solidified body is first repaired with a geopolymer slurry and then coated with a coating material.

[0026] Preferably, the curing and molding conditions include: firstly placing it naturally at room temperature for 1 to 3 days, and then further curing it in an environment of 30 to 50° C. for 3 to 7 days.

[0027] The present invention provides a geopolymer, comprising the following raw materials: a main material, glass fiber, nano silicon dioxide and a composite alkali activator; the main materials are metakaolin, slag and bentonite; the mass ratio of the metakaolin, slag and bentonite is 1:1:0.375; the mass of the glass fiber is 2% of the total mass of the main material; the mass of the nano silicon dioxide is 3% of the total mass of the main material; the mass of the composite alkali activator is 15% of the total mass of the main material. Bentonite has good adsorption, expansion and plasticity. The present invention enhances the adsorption performance and stability of the geopolymer by using bentonite; improves the toughness and crack resistance of the geopolymer by using glass fiber; and nano silicon dioxide provides active adsorption sites to improve adsorption selectivity. The coordinated action of each component gives the geopolymer good nuclide adsorption, and improves the compressive strength and long-term stability of the geopolymer solidified body. The present invention has a good curing effect on a variety of radioactive nuclides (such as uranium, strontium, cesium, etc.).

[0028] The present invention provides a method for solidifying radioactive waste liquid with a geopolymer as described in the above scheme, comprising the following steps: mixing a main material, glass fiber, nano-silicon dioxide and a composite alkali activator to obtain a mixture; mixing the mixture with radioactive waste liquid to obtain a geopolymer slurry; solidifying and molding the geopolymer slurry to obtain a first solidified body; and subjecting the first solidified body to a thermal activation treatment. The present invention can further promote the chemical reaction inside the geopolymer by adding a thermal activation treatment, improve its strength and stability, and also improve its solidification effect on radioactive nuclides.

[0029] In addition, traditional radioactive waste liquid solidification treatment usually requires multiple steps such as pre-treatment of the waste liquid and then mixing with a solidifying agent. The present invention uses radioactive waste liquid directly as the liquid part of the geopolymer, which can organically combine the waste liquid treatment with the geopolymer preparation process, reduce the process flow of separate waste liquid treatment, simplify the operation steps, improve the overall treatment efficiency, reduce the operational errors and secondary pollution risks caused by complex processes, and is more conducive to large-scale engineering applications.

[0030] Furthermore, after completing the thermal activation treatment, the present invention also includes coating a coating material on the surface of the obtained second solidified body, so that the anti-leaching performance of the geopolymer solidified body is greatly improved, and a good solidification effect is achieved for a variety of radioactive nuclides (such as uranium, strontium, cesium, etc.), which greatly reduces the risk of leakage of radioactive nuclides and ensures the safety protection of the environment during storage and disposal. DETAILED DESCRIPTION

[0031] The present invention provides a geopolymer, comprising the following preparation raw materials: a main material, glass fiber, nano silicon dioxide and a composite alkali activator;

[0032] The main ingredients are metakaolin, slag and bentonite; the mass ratio of the metakaolin, slag and bentonite is 1:1:0.375;

[0033] The mass of the glass fiber is 2% of the total mass of the main material;

[0034] The mass of the nano silicon dioxide is 3% of the total mass of the main material;

[0035] The mass of the composite alkali activator is 15% of the total mass of the main material.

[0036] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0037] The raw materials for preparing the geopolymer provided by the present invention include main materials, wherein the main materials are metakaolin, slag and bentonite; the mass ratio of the metakaolin, slag and bentonite is 1:1:0.375.

[0038] In the present invention, the metakaolin is preferably obtained by dehydrating kaolin and then subjecting it to secondary calcination; the temperature of the secondary calcination is preferably 800-900°C, and the time is preferably 2-4h. The present invention has no special requirements for the temperature of the dehydration, and the dehydration temperature well known in the art can be used. In the present invention, the metakaolin obtained after the kaolin is dehydrated is the metakaolin well known in the art. The difference from the commonly used metakaolin is that the present invention is subjected to secondary calcination. In a specific embodiment, the temperature of the secondary calcination can be 800°C, 850°C or 900°C, and the time of the secondary calcination can be 2h, 3h or 4h. The present invention improves the crystallinity and activity of metakaolin by secondary calcination. In the present invention, the metakaolin is the main aluminosilicate source of geopolymer.

[0039] In the present invention, the slag is preferably waste slag from steel smelting or other metallurgical industries, rich in oxides such as calcium, magnesium, silicon, aluminum, etc., to provide additional chemical activity and structural stability for geopolymers. In the present invention, the slag is preferably waste slag from steel smelting or other metallurgical industries obtained by sieving after magnetic separation or flotation treatment. The present invention has no special requirements for the magnetic separation and flotation process, and the magnetic separation and flotation processes well known in the art can be used. The present invention removes metallic iron particles and other low-density impurity components therein by magnetic separation or flotation. The present invention removes metallic iron particles to prevent metallic iron from reacting with alkali in the subsequent alkali excitation process, consuming alkali exciters, and affecting the reaction process and curing effect of geopolymers. Moreover, the presence of metallic iron particles may cause uneven internal structure of the solidified body, reducing the strength and stability of the solidified body. By removing other low-density impurity components, such as residual coal, sawdust and other organic matter, unreacted ore impurities, such as some quartz, feldspar and other gangue minerals; avoiding the possibility of combustion or decomposition of organic matter during alkali excitation, generating gas, resulting in pores and defects inside the solidified body, affecting the quality and performance of the solidified body, and the activity of ore impurities is relatively low, and excessive presence will dilute the active components in the slag and reduce the reactivity of the slag. In the present invention, the particle size of the slag is preferably 0.1 to 1 mm.

[0040] In the present invention, the mass content of montmorillonite in the bentonite is preferably above 70%. In the present invention, the bentonite has good adsorption, expansion and plasticity, and can enhance the adsorption performance and stability of geopolymers.

[0041] In the present invention, the metakaolin, slag and bentonite are used as main materials to provide aluminosilicate. The present invention improves the activity of the alkali-induced reaction by controlling the mass ratio of the three to 1:1:0.375.

[0042] The raw materials for preparing the geopolymer provided by the present invention include glass fibers. In the present invention, the glass fibers are used to improve the toughness and crack resistance of the geopolymer.

[0043] The raw material for preparing the geopolymer provided by the present invention includes nano-silicon dioxide. In the present invention, the nano-silicon dioxide can provide active adsorption sites and improve adsorption selectivity.

[0044] The raw materials for preparing the geopolymer provided by the present invention include a composite alkali activator; the composite alkali activator preferably includes solid water glass and alkali metal hydroxide; the modulus of the solid water glass is preferably 1.5 to 2.0; in a specific embodiment, the modulus of the solid water glass can be 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0. In the present invention, the alkali metal hydroxide preferably includes sodium hydroxide or potassium hydroxide; the mass ratio of the solid water glass to the alkali metal hydroxide is preferably 5:1. In the present invention, although the water glass as an alkali activator can solidify the geopolymer to a certain extent, when used alone, its early strength development is relatively slow. The present invention adopts a composite alkali activator to promote the reaction of the geopolymer faster and accelerate the formation of early strength, which is crucial for the rapid solidification and stabilization treatment of radioactive waste liquid, and can reduce the processing time and reduce potential risks.

[0045] The components of the present invention cooperate to give the geopolymer good nuclide adsorption, have good curing effect on various radioactive nuclides (such as uranium, strontium, cesium, etc.), and improve the compressive strength and long-term stability of the geopolymer solidified body.

[0046] The present invention provides a method for solidifying radioactive waste liquid by using a geopolymer as described in the above scheme, comprising the following steps:

[0047] The main material, glass fiber, nano silicon dioxide and composite alkali activator are mixed to obtain a mixture;

[0048] mixing the mixed material with radioactive waste liquid to obtain a geopolymer slurry;

[0049] Curing the geopolymer slurry into a shape to obtain a first cured body;

[0050] The cured body is subjected to a heat activation treatment.

[0051] The invention mixes the main material, glass fiber, nano silicon dioxide and a composite alkali activator to obtain a mixture.

[0052] In the present invention, the mixing preferably includes: first mixing the main material, glass fiber and nano-silicon dioxide, then adding the composite alkali activator to the obtained mixture under stirring conditions, and continuing to stir. In the present invention, the stirring rate is preferably 800-1200rpm, and after the addition of the composite alkali activator is completed, preferably continue stirring for 10-20min. In the present invention, the composite alkali activator is preferably added slowly.

[0053] After obtaining the mixed material, the present invention mixes the mixed material with radioactive waste liquid to obtain geopolymer slurry.

[0054] In the present invention, the mass of the radioactive waste liquid is preferably 30-50% of the total mass of the main material, and in specific embodiments it can be 30%, 35%, 40%, 45% or 50%. The present invention has no special requirements for the radioactive waste liquid, and any radioactive waste liquid known in the art can be used. In a specific embodiment, the radioactive waste liquid is a low-level radioactive waste liquid taken from a radioactive wastewater storage pool, with a total specific activity of 3.4×104Bq·L-1, and the main radionuclides are 137 Cs and 241 Am.

[0055] The present invention uses radioactive waste liquid directly as the liquid part of the geopolymer, which can organically combine the waste liquid treatment with the geopolymer preparation process, reduce the process flow of separate waste liquid treatment, simplify the operation steps, improve the overall treatment efficiency, reduce the operational errors and secondary pollution risks caused by complex processes, and is more conducive to large-scale engineering applications. In the present invention, the mixing is preferably carried out in a mixer. The present invention preferably gradually adds the radioactive waste liquid to the mixture, and stirs for 20 to 30 minutes after the addition is completed.

[0056] After adding radioactive waste liquid, the main materials and additives (nano-silica, glass fiber) form geopolymers under alkaline excitation conditions. The geopolymers wrap the radionuclides in the radioactive waste liquid in a unique three-dimensional network structure through physical adsorption, chemical precipitation and ion exchange, thereby reducing the mobility and leaching of the radionuclides and achieving harmless treatment of the radioactive waste liquid.

[0057] After obtaining the geopolymer slurry, the present invention solidifies the geopolymer slurry to obtain a first solidified body.

[0058] In the present invention, the curing and molding conditions preferably include: first naturally placed at room temperature for 1 to 3 days, and then further cured in an environment of 30 to 50°C for 3 to 7 days. In a specific embodiment, the slurry can be initially cured by naturally placing it at room temperature for 1 day, 2 days or 3 days, and then transferred to an environment of 30°C, 40°C or 50°C for further curing for 3 days, 4 days, 5 days, 6 days or 7 days. The present invention preferably pours the geopolymer slurry into a pre-prepared mold for curing and molding. The present invention has no special requirements for the shape and size of the mold, which can be selected according to actual application requirements, such as columnar, block or other specific shapes.

[0059] After obtaining the first solidified body, the present invention performs a thermal activation treatment on the first solidified body to obtain a second solidified body.

[0060] In the present invention, the temperature of the thermal activation treatment is preferably 200-600°C, and the time is preferably 2-12h; the thermal activation treatment is preferably carried out in an air atmosphere. In a specific embodiment, the temperature of the thermal activation treatment may be 200°C, 300°C, 400°C, 500°C or 600°C; the time of the thermal activation treatment may be 2h, 4h, 6h, 8h, 10h or 12h. In the present invention, the rate of heating to the temperature of the thermal activation treatment is preferably below 5°C, more preferably 3-5°C / min. After the thermal activation treatment is completed, the obtained second solidified body is cooled to room temperature. In the present invention, the cooling rate is preferably below 5°C, more preferably 3-5°C / min. In a specific embodiment, the present invention is naturally cooled to room temperature with the furnace to control the heating rate below 5°C. The present invention can further promote the chemical reaction inside the geopolymer through thermal activation treatment, improve its strength and stability, and also improve its curing effect on radionuclides.

[0061] The present invention controls the heating rate and cooling rate of the thermal activation treatment to avoid cracking of the second solidified product due to excessively rapid temperature changes.

[0062] After obtaining the second solidified body, the present invention preferably coats a coating material on the surface of the second solidified body; if there are holes and / or cracks on the surface of the second solidified body, the second solidified body is first repaired with a geopolymer slurry and then coated with a coating material.

[0063] The present invention preferably first cleans the surface of the second solidified body to observe whether there are holes and / or cracks. The present invention has no special requirements for the cleaning process, and can remove dust, impurities and possible loose particles on the surface to ensure that the surface is flat and clean. The present invention improves the adhesion between the coating and the second solidified body through cleaning.

[0064] The invention improves the anti-leaching performance of the polymer solidified body and prevents the leaching of nuclides by repairing and coating the coating material.

[0065] The present invention has no special requirements for the coating material. A suitable coating material is selected according to the nuclides to be processed to achieve the purpose of preventing nuclides from leaking. In the embodiment of the present invention, epoxy resin coating is specifically used.

[0066] In the present invention, the coating is preferably spraying. The pressure of the spraying is preferably 0.3-0.6 MPa, the distance of the spraying is preferably 15-30 cm, and the moving speed of the spray gun is preferably 0.3-0.5 m / s. In a specific embodiment, the pressure of the spraying can be 0.3 MPa, 0.4 MPa, 0.5 MPa or 0.6 MPa, the distance of the spraying can be 15 cm, 20 cm, 25 cm or 30 cm, and the moving speed of the spray gun can be 0.3 m / s, 0.4 m / s or 0.5 m / s.

[0067] The present invention preferably starts from one end of the second solidified body and sprays the coating material uniformly to ensure uniform coating thickness and avoid sagging, spray leakage and the like.

[0068] The geopolymer and the method for solidifying radioactive waste liquid provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0069] Example 1

[0070] The commercially available metakaolin was subjected to secondary calcination, specifically calcined at 800°C for 3h, and then set aside;

[0071] Slag: The metal iron particles and other low-density impurities are removed by magnetic separation. The treated slag is sieved and particles with a particle size range of 0.1 to 1 mm are selected for use;

[0072] Weigh the main materials according to the mass ratio of metakaolin, slag and bentonite (montmorillonite content is 72%) of 1:1:0.375;

[0073] Weigh glass fiber and nano-silicon dioxide as two additives, respectively, according to 2% and 3% of the total mass of the main material;

[0074] Put the main ingredients, glass fiber and nano-silica into a mixer, start stirring, and slowly add 15% of the total weight of the main raw materials (solid water glass with a modulus of 1.6 and sodium hydroxide, the mass ratio of the two is 5:1), stir at a speed of 1000 rpm for 15 minutes to make the solid raw materials and the alkali activator preliminarily mixed;

[0075] Gradually add 40% of the total mass of the main material radioactive waste liquid (low-level radioactive waste liquid, taken from a radioactive wastewater storage pool, colorless and transparent solution, with a total specific activity of 3.4×10 4 Bq·L -1 The main radionuclides are 137 Cs and 241 Am), and continue stirring for 20 min to ensure that the radioactive waste liquid is fully mixed with other raw materials to form a uniform slurry;

[0076] Pour the stirred slurry into a pre-prepared mold in the shape of a Φ35cm×50cm cylinder. Leave it naturally at room temperature for 3 days to allow the slurry to initially solidify, and then transfer it to a 30°C environment for further solidification for 7 days to ensure that the geopolymer is fully solidified and formed to obtain the first solidified body;

[0077] The first solidified body is placed in a thermal activation furnace, heated to 500°C at a rate of 3°C / min for 12 hours, and then the heating is turned off and the temperature is naturally lowered to room temperature along with the furnace to obtain a second solidified body;

[0078] Clean the surface of the second solidified body to remove dust, impurities and possible loose particles on the surface, ensure that the surface is flat and clean, so as to improve the adhesion between the coating and the solidified body; check whether there are defects such as cracks and holes on the surface of the solidified body. For minor defects, a small amount of geopolymer slurry can be used to fill the holes, and compact and smooth them with tools, and repair them appropriately;

[0079] Load the prepared epoxy resin coating into the spray gun and start spraying at a pressure of 0.3MPa. Keep the spraying distance at 20cm and the moving speed of the spray gun at 0.3m / s. Start from one end of the solidified body and spray the epoxy resin evenly to ensure that the coating thickness is uniform and avoid sagging, missing spraying and other phenomena.

[0080] After being treated by the above method, the radioactive nuclides are effectively solidified, and the formed geopolymer solidified body has high compressive strength, good long-term stability, and can effectively prevent nuclides from leaching.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A geopolymer, characterized in that: The preparation comprises the following raw materials: main material, glass fiber, nano silicon dioxide and composite alkali activator; The main ingredients are metakaolin, slag and bentonite; the mass ratio of the metakaolin, slag and bentonite is 1:1:0.375; The mass of the glass fiber is 2% of the total mass of the main material; The mass of the nano silicon dioxide is 3% of the total mass of the main material; The mass of the composite alkali activator is 15% of the total mass of the main material.

2. The geopolymer according to claim 1, characterized in that The composite alkali activator comprises solid water glass and alkali metal hydroxide; The modulus of the solid water glass is 1.5 to 2.0; The mass ratio of the solid water glass to the alkali metal hydroxide is 5:

1.

3. The geopolymer according to claim 1, characterized in that The mass content of montmorillonite in the bentonite is above 70%.

4. The geopolymer according to claim 1, characterized in that The metakaolin is obtained by dehydrating kaolin and then subjecting it to secondary calcination; the temperature of the secondary calcination is 800-900° C., and the time is 2-4 hours.

5. A method for solidifying radioactive waste liquid using the geopolymer according to any one of claims 1 to 4, characterized in that: The following steps are involved: The main material, glass fiber, nano silicon dioxide and composite alkali activator are mixed to obtain a mixture; mixing the mixed material with radioactive waste liquid to obtain a geopolymer slurry; Curing the geopolymer slurry into a shape to obtain a first cured body; The first solidified body is subjected to a heat activation treatment.

6. The method according to claim 5, characterized in that The mass of the radioactive waste liquid is 30-50% of the total mass of the main material.

7. The method according to claim 5, characterized in that The temperature of the thermal activation treatment is 200-600° C., and the time is 2-12 hours.

8. The method according to claim 5 or 7, characterized in that: The rate of increasing the temperature to the temperature of the thermal activation treatment is below 5°C.

9. The method according to claim 5 or 7, characterized in that: After completing the heat activation treatment, the method further includes coating a coating material on the surface of the obtained second solidified body; if there are holes and / or cracks on the surface of the obtained second solidified body, the second solidified body is first repaired with a geopolymer slurry and then coated with a coating material.

10. The method according to claim 5, characterized in that The curing molding conditions include: firstly placing the material naturally at room temperature for 1 to 3 days, and then further curing the material at 30 to 50° C. for 3 to 7 days.